Optimal Tilt Angle for Fixed PV Panels for Annual Maximum Energy Output in Cyprus Condition - Reza, Amjadi, Hamid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Solar panel technology system utilizes solar radiation to generate electricity, and it is very important to absorb and capture maximum energy output. This study aims to find the yearly optimal tilt angle to maximize the cumulative energy output. This study was conducted in Cyprus, and the solar panel true in the south, because Cyprus is in the Northern Hemisphere, and the solar panel should be in the south. During the research, several methods considering different conditions such as clearness index, extraterrestrial radiation on a tilted surface, ground reflection were discussed, and then the results of each method based on Cyprus latitude is observed. The Rhino 3D program and the Grasshopper plug-in program have been used to find maximum solar radiation and the optimum tilt angle. The data for this study were collected from the Energy Plus Weather data website. The data are used to calculate and evaluate the beam and diffuse and ground-reflected solar radiation and total solar radiation for different tilt angles between 0 º and 90º and the value of 180º for azimuth angle by Tilt and Orientation Factor component inside the Grasshopper. By using the program, the total maximum solar radiation is about 2075 kWh/m2, and the optimum tilt angle is approximately 29º Keywords: Solar Panels, Optimum Tilt Angle, Solar Radiation, Azimuth

ÖZ: Güneş enerjısi teknoloji sistemleri güneş ışığını kullanarak elektrik enerjisi üretirler. Azami enerji çıktısı içın Güneş enerjısi yakalayabilmek çok önemlidir. Bu çalışmanın amacı yıllık toplam enerji çıktısının azami olabılmesi için gerekli optimal panel açısını belirlemektir. Bu çalışma Kıbrıs için yapılmıştır. Güneş paneli gerçek güneye bakacak şekilde sabitlenmiştir. Araştırma sırasında, netlik endeksi, eğim yütyine düşen güneş ışığını, zemin yansıması gibi faktörler ele alınmıştır. Rhino 3D programı ve Grasshopper program eki kullanılarak gerekli hesaplamalar yapılmış, optimal eğim açısı bulunmuştur. Bu çalışmanın verileri "Energy Plus Weather" veri web sitesinden toplanmıştır. Yerden yansıyan, direk ve dağınık güneş ısığı 0º ile 90º derece eğim açıları ve 180º azimuth açıları için hesaplanmıştır. Bu çalışma neticesinde en çok enerji çıktası alınabilen (2075 kwh/m2) panel eğim açısının yaklaşık 29º olduğu hesaplanmıştır. AnahtarKelimeler: Solar panel, Optimal eğim açısı, Güneş ışığını, Azimuth
Master of Science in Electrical and Electronic Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2021. Supervisor: Assist. Prof. Dr. Davut Solyalı.
Keywords: Electrical and Electronic Engineering; Solar Energy-Cyprus; Photovoltaic power generations; Solar Energy Engineering; Photovoltaic power systems - Solar energy--Solar power plants; Solar Panels; Optimum Tilt Angle; Solar Radiation; Azimuth